The Effectiveness of SGLT-2 Inhibitors vs GLP-1 Receptor Agonists in Enhancing Kidney Function and Glycemic Control for Diabetes Mellitus Patients with CKD: A Narrative Review - Wibawa, Putu Ngurah Pradnya; Ekayanti, Ni Luh Putu Serly (Babali Publisher, 2026)
Introdution: Type 2 Diabetes Mellitus (T2DM) and Chronic Kidney Disease (CKD) are highly interconnected, impacting global health. Sodium-Glucose Cotransporter-2 Inhibitors (SGLT2i) and Glucagon-Like Peptide-1 Receptor Agonists (GLP-1RAs) offer promising benefits for glycemic control, cardiovascular health, and kidney protection. This review compares their effectiveness in enhancing kidney function and glycemic control for T2DM patients with CKD. Methods: A narrative review was conducted using the PICO framework, searching the PubMed database and online search (ScienceDirect and Google Scholar) for English-language observational research articles published between 2020 and 2025. Articles focused on SGLT2i and GLP-1RA therapies in T2DM patients with CKD, assessing kidney function and glycemic control. Fifteen articles were selected from an initial 706. The keyword use is “comparing” AND “effectiveness” AND “SGLT-2 inhibitor” AND “GLP-1 RA” AND “kidney function” AND “glycemic control” AND “T2DM” AND “CKD” AND “patients”. Results: SGLT2 inhibitors consistently demonstrated strong renal protective effects, including slower eGFR decline and reduced kidney failure progression. GLP-1RAs excelled in glycemic control, weight management, and cardiovascular event reduction. While SGLT2i generally appeared superior for direct renal protection, some studies suggested comparable renal outcomes. Real-world data largely supported these findings, enhancing clinical applicability. Conclusion: SGLT2 inhibitors are recommended for T2DM patients with CKD, especially those at higher renal risk. GLP-1RAs are valuable for glycemic control, weight, and cardiovascular benefits. Their complementary mechanisms suggest potential for additive benefits in combination therapy, necessitating further research to optimize patient outcomes.